Code-Switching in Asian EFL Classroom and the Teachers` Perception - Yora Yalu Setio Wibowo Sasongko (k@ta: A Biannual Publication on the Study of Languange and Literature, 2023)
There are many pros and cons related to the use of code-switching in EFL class. The use of code-switching, according to Khaerunnisa (2016) is considered as a useful instrument to help students and teacher in EFL class. In contrast, Macaro (2005) explains that the use of code-switching in EFL class is not sufficient to support students` development in mastering L2 when teachers keep using L1 in their deliverance. This research aims to discuss how teachers react to the use of code switching in class. Furthermore, this research reveals the role of code-switching through the use of it in EFL class. Moreover, the data in this research are taken from scientific articles in three different countries in Asia, namely Indonesia, Pakistan, and Turkey, therefore library research is applied as the technique of data collecting in this research. The data analysis shows that the use of code-switching in three countries have various use and function. The finding shows that In Indonesia and Turkey, the use of code-switching in EFL class is part of teaching method that enables the teachers to explain the lesson comprehensively. Meanwhile, the use of code-switching in Pakistan tends to be implemented as an instrument to build teachers-students engagement.